Intelligent Collaborative Control of Mobile Robots for Emergency and Rescue Operations Within the Industry 5.0 Paradigm - Yevsieiev, V. (ХНУРЕ, 2026)
The paper considers an approach to intelligent collaborative control of mobile robots for emergency and rescue operations within the Industry 5.0 paradigm. A human-centered cyberphysical system architecture is proposed that combines autonomous motion planning, adaptive control, and operator involvement in the decision-making loop. The use of sensor fusion and a digital twin of the environment improves the reliability of navigation under uncertainty and partial observability. The results of numerical simulations demonstrate increased motion safety and control stability compared to deterministic approaches
Keywords: collaborative robots; Industry 5.0; adaptive control; digital twin; civil safety